Perioperative anesthetic management in total abdominal hysterectomy due to uterine fibroid in a patient with severe aortic stenosis. A case report - Yuliel Varona Rodríguez; José Carlos Acosta Abad; Adonis Cintra Dornes; Liliam María Castillo Manresa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
The case of a 35-years-old female patient with a history of presenting a murmur since childhood and who had to undergo surgery for uterine fibroid is presented. The anesthesiologist, during the preoperative consultation, verified the aforementioned murmur, so it was decided to postpone surgery and consult with a cardiologist. The echocardiographic examination showed that the patient had severe aortic stenosis with preserved ejection fraction, stress test: functional class I, without ischemia. Using orotracheal general anesthesia, a total abdominal hysterectomy was performed without complications. The perioperative management of aortic stenosis is of vital importance for the anesthesiologist.